Exosomal CircRNAs in Circulation Serve as Diagnostic Biomarkers for Acute Myocardial Infarction - Xiaoyan Liu; Yeping Zhang; Wen Yuan; Ruijuan Han; Jiuchang Zhong; Xinchun Yang; Meili Zheng; Boqia Xie (Frontiers in Bioscience-Landmark, 2024)
Background: The diagnostic potential of circular RNAs (circRNAs) in circulating exosomes for acute myocardial infarction (AMI) is not well understood, despite existing research indicating their role in cardiovascular diseases. This study aimed to clarify the significance of exosomal circular RNAs as indicators for AMI. Methods: We examined 120 individuals diagnosed with AMI and 83 individuals with non-cardiogenic chest pain (NCCP), all previously enrolled in a conducted study. High-throughput sequencing to identify differentially expressed circRNAs in the circulating exosomes of AMI patients. To validate, we employed Real-Time polymerase chain reaction (RT-PCR) targeting five circRNAs that exhibited notable increase. Results: The sequencing identified 893 exosomal circRNAs with altered expression in AMI patients, including 118 up-regulated and 775 down-regulated circRNAs. Genes linked to these circRNAs were enriched in crucial Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, highlighting their direct relevance to AMI pathophysiology. Three exosomal circRNAs (hsa_circ_0001558, hsa_circ_0001535, and hsa_circ_0000972) showed significant up-regulation in AMI patients during the initial validation cohort. The corresponding area under the curve (AUC) values were 0.79, 0.685, and 0.683, respectively. Further validation of hsa_circ_0001558 in a second cohort showed a 4.45-fold increase in AMI patients, with AUC = 0.793. The rise was particularly noticeable in patients with non-ST-elevation myocardial infarction (NSTEMI) (2.80 times, AUC = 0.72) and patients with ST-elevation myocardial infarction (STEMI) (5.27 times, AUC = 0.831) compared to patients with NCCP. Conclusions: Our findings demonstrate significant differences in the expression patterns of circRNAs in plasma exosomes between AMI patients and NCCP patients. Specifically, hsa_circ_0001558 appears as a promising indicator for AMI diagnosis. Further research is necessary to fully evaluate the diagnostic potential of exosomal circRNAs in the context of AMI, emphasizing the importance of these findings.